The physiology of crop yield - Hay, Robert K. M. (Blackwell Pub, 2006)
The book focuses on the many advances in crop physiology, within a framework of resource capture and use. Retaining the central core of the first edition, this long-awaited second edition draws on recent developments in areas such as phenology, canopy dynamics and crop modelling, and the concepts of sustainable crop production. A broad perspective is developed, from the gene through the plant and crop to the ecosystem, covering 1)Advances in molecular biology relating to crop science, 2)Limitation of crop yield by the supply of water or nitrogen 3) Global climate change and its impact on crop modelling 4) Physiological aspects of crop quality 5) A wider range of species, with emphasis on wheat, maize and soybean